Characterisation of β-lactoglobulin nanoparticles and their binding to caffeine. (October 2017) - Guo, Yuchen; Harris, Peter; Kaur, Amanpreet; Pastrana, Lorenzo; Jauregi, Paula
Abstract: The production of β-Lg nanoparticles by a simple heat-induced denaturation method without the need to add chemicals was performed at different conditions of pH, and temperature of denaturation. Optimum conditions were set as 0.2% β-Lg, pH 6 and simply heating at 75 °C for 45 min. At these conditions, a monodisperse solution with colloidal stability was obtained and the yield of aggregation was over 90%. Shape and size of nanoparticles were determined by Dynamic Light Scattering and by electron microscopy. A monodisperse particle size distribution of spherical shape particles (200 nm-300nmin diameter) was obtained. The stability of the aggregates towards various types of dissociating buffers was studied. Sodium dodecyl sulphate (SDS) and urea had a strong effect on the size of the nanoparticles, while 2-Mercaptoethanol and Dithiothreitol (DTT) had no significant effect. Therefore hydrogen bonding and hydrophobic interactions were the predominant interactions responsible for the microstructure. Maximum yield of caffeine encapsulation of 13.54% was obtained at caffeine to β-Lg molar ratio of 50:1. Rapid nanoparticle degradation and increase in polydispersity during the incubation of β-Lg nanoparticles at simulating stomach conditions was observed due to enzymatic attack. Nevertheless, little release of entrapped caffeine was noted. Total release was achieved at intestinal conditions. Finally, the adsorption of caffeine to both native and denatured β-Lg followed a Langmuir adsorption isotherm model and caffeine had three times more affinity for partially denatured β-Lg in nanoparticles than for native protein. Graphical abstract: Highlights: 200-300 nm β-Lg nanoparticles produced by a simple heat-induced denaturation method. An improved understanding of the mechanism of aggregate formation was obtained. Maximum yield of caffeine encapsulation was 13%. About 30% of caffeine released at SGF conditions but complete released at intestinal conditions. Caffeine binding to protein followed Langmuir model.